(3QSGdI GdUdGIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi NU GddEfSGf HCTQa GdNWGH CeG HYO deG EdJeSJ efi CjgG GdCN Cf CcJH dc QSGdI ai GdUdGI s
(3BNQgG (B:s
(3Ydi GdYGbd GdaGVd GdcGed Sdhc WQjb GdJYHO hGdeOGheg Ydi GdUdGg JeJ GdQSGdI HYhf ajGV GdLhO heSJMb GdMeO Gdedc GdeYHhO hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B30s
(3GdfSNI HgG MhGTs
(3HChdg fbhd eNJdaI Ydi UaMg GdYfhGfs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs